Pharmacology, efficacy and safety of liraglutide in the management of type 2 diabetes - Joshua J Neumiller (Dove Medical Press, 2010)
Joshua J Neumiller1, Travis E Sonnett2, Lindy D Wood1, Stephen M Setter1, R Keith Campbell21Department of Pharmacotherapy, College of Pharmacy, Washington State University, Spokane, Washington; 2Department of Pharmacotherapy, College of Pharmacy, Washington State University, Pullman, Washington, USAAbstract: Liraglutide is a glucagon-like peptide-1 analog with pharmacokinetic properties suitable for once-daily administration approved by the Food and Drug Administration for the treatment of patients with type 2 diabetes. Clinical trial data from large, controlled studies demonstrate the safety and efficacy of liraglutide in terms of hemoglobin A1c (HbA1c) reduction, reductions in body weight, and the drug’s low risk for hypoglycemic events when used as monotherapy. Liraglutide has been studied as monotherapy and in combination with metformin, glimepiride, and rosiglitazone for the treatment of type 2 diabetes. Additionally, comparative data with insulin glargine and exenatide therapy are available from Phase III trials. Once-daily administration may provide a therapeutic advantage for liraglutide over twice-daily exenatide, with similar improvements in HbA1c and body weight observed when liraglutide was compared with exenatide. The glucose-dependent mechanism of insulin release with incretin analog therapy holds potential clinical significance in the management of postprandial hyperglycemic excursions, with minimal risk of hypoglycemia when used with non-secretagogue medications. Data to date on patient-reported outcomes with liraglutide treatment are encouraging. The most common adverse events associated with liraglutide therapy are dose-dependent nausea, vomiting, and diarrhea. Diligent postmarketing surveillance to elucidate the risk of pancreatitis and medullary thyroid carcinoma in a heterogeneous population are likely warranted.Keywords: incretin analog, incretin effect, liraglutide, diabetes